Digital Marketing Trends and Their Effectiveness in Reaching Gen Z Consumers - PA Andiena Nindya Putri; Yenni Kurnia Gusti; Loso Judijanto; Renny Lubis; Bekti Utomo (Dinasti International Journal of Education Management And Social Science, 2024)
In the evolving landscape of digital marketing, understanding the preferences and behaviors of Generation Z (Gen Z) is crucial for businesses aiming to engage this tech-savvy demographic. This article conducts a comprehensive literature review to explore current digital marketing trends and assess their effectiveness in reaching Gen Z consumers. Drawing from a wide array of sources, the study examines key trends such as social media marketing, influencer collaborations, personalized content, and interactive experiences. The review highlights that Gen Z values authenticity, immediacy, and interactivity, with platforms like TikTok, Instagram, and YouTube playing pivotal roles in their digital consumption. Additionally, the article discusses the importance of mobile optimization and the growing influence of ephemeral content in capturing Gen Z's short attention span. The findings suggest that marketers must adopt a multi-faceted approach, leveraging data analytics and real-time engagement strategies to resonate with this dynamic cohort. This review provides valuable insights for marketers seeking to refine their digital strategies and build meaningful connections with Gen Z consumers.